2014
DOI: 10.2527/jas.2013-7364
|View full text |Cite
|
Sign up to set email alerts
|

Digesta sampling sites and marker methods for estimation of ruminal outflow in bulls fed different proportions of corn silage or sugarcane1

Abstract: The objective of this experiment was to assess ruminal outflow and apparent total-tract digestibility using digesta samples from 3 sites (reticulum, omasum, and abomasum) and 3 marker methods (single marker: indigestible NDF [iNDF; sample without separation]; double marker: iNDF + Co-EDTA [filtered sample]; and triple marker: iNDF + ytterbium [Yb] acetate + Co-EDTA [filtered and centrifuged]) in bulls fed corn silage and sugarcane-based diets. Eight crossbred (Holstein × Zebu) bulls (353 ± 37 kg of BW; 24 ± 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 31 publications
1
25
1
4
Order By: Relevance
“…Studies comparing reticular and duodenal sampling (Hristov, 2007), and reticular and omasal sampling (Krizsan et al, 2010b), using triple-marker techniques at both sites, showed similar flows of NAN, NANMN, and microbial NAN, and ruminal digestibility of NAN for both methods. In contrast, Rotta et al (2014) comparing reticular, abomasal, and omasal sampling reported that the flow of CP was lower for reticular than omasal sampling with abomasal being intermediate. Ruminal digestibility of CP was higher based on reticular sampling compared with the other 2 sites, which did not differ.…”
Section: Invasive or Direct Methods For Assessing Feed Protein Degradmentioning
confidence: 88%
See 1 more Smart Citation
“…Studies comparing reticular and duodenal sampling (Hristov, 2007), and reticular and omasal sampling (Krizsan et al, 2010b), using triple-marker techniques at both sites, showed similar flows of NAN, NANMN, and microbial NAN, and ruminal digestibility of NAN for both methods. In contrast, Rotta et al (2014) comparing reticular, abomasal, and omasal sampling reported that the flow of CP was lower for reticular than omasal sampling with abomasal being intermediate. Ruminal digestibility of CP was higher based on reticular sampling compared with the other 2 sites, which did not differ.…”
Section: Invasive or Direct Methods For Assessing Feed Protein Degradmentioning
confidence: 88%
“…Consequently, the contribution of soluble N components (protein, peptides, and free AA), microbial populations (liquid and particle associated bacteria, protozoa, and fungi), and insoluble dietary N components to N flow from the reticulorumen can be determined (Ahvenjärvi, 2006). Studies that have directly compared N flows using omasal and duodenal sampling indicate that they are comparable (Ahvenjärvi et al, 2000;Rotta et al, 2014), although in the study of Ahvenjärvi et al (2000) where microbial NAN was also determined, it tended to be higher in the omasal canal than in the duodenum. Roman-Garcia et al (2016) in a meta-analysis reported a greater microbial N and smaller NANMN flows for omasal sampling than for duodenal sampling.…”
Section: Invasive or Direct Methods For Assessing Feed Protein Degradmentioning
confidence: 96%
“…Digesta flow into the abomasum was estimated with the double marker method, using indigestible NDF (iNDF) and Co-EDTA (Rotta et al, 2014). As a fluid marker, 5 g/d of Co-EDTA (420 mg of Co/d) was divided into 4 doses and infused into the rumen cannula in equidistant times (0600, 1200, 1800, and 2400 h) from d 7 through 12 of each period.…”
Section: Experimental Procedures and Sample Collectionsmentioning
confidence: 99%
“…A continuous infusion of 5 g/day of Co-EDTA (0.7 g cobalt/day) from the 1 st to the 6 th day of collection was performed during each period (first period: 145-150 days of gestation, second period: 200-205 days of gestation, and third period 255-260 days of gestation) using 2 peristaltic pumps (model BP-600.4, Colombo, Paraná, Brazil). A total of 8 samples per animal were collected from the omasum at a 9-h interval for 3 days; sampling times were 0200, 0500, 0800, 1100, 1400, 1700, 2000, and 2300 h. The technique, that was developed by Huhtanen [13] and adapted by Leão [14], was used for sampling of the omasal digesta, where approximately 250 mL of digesta was used for a bacterial isolate and 500 mL was used for the ruminal flow estimation [15]. The samples were stored in plastic containers at -20 °C for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of each experimental period, samples of omasal digesta were thawed at room temperature and one composite was created per animal, following the recommendations of Rotta [15]. Thus, 4 L were obtained to estimate the omasal flow, which was filtered using a 100 μm nylon filter with an open area of 44% (Sefar Nytex 100/44; Sefar, Thal, Switzerland), thereby obtaining two phases: liquid particles and solid particles.…”
Section: Methodsmentioning
confidence: 99%